Proceedings of Advancing Astrophysics With the Square Kilometre Array — PoS(AASKA14) 2015
DOI: 10.22323/1.215.0173
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling lifecycles and physics of radio-loud AGN in the SKA Era

Abstract: Radio-loud AGN (> 10 22 W Hz −1 at 1.4 GHz) will be the dominant bright source population detected with the SKA. The high resolution that the SKA will provide even in wide-area surveys will mean that, for the first time sensitive, multi-frequency total intensity and polarisation imaging of large samples of radio-loud active galactic nuclei (AGN) will become available. The unprecedented sensitivity of the SKA coupled with its wide field of view capabilities will allow identification of objects of the same morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 107 publications
1
14
0
Order By: Relevance
“…In any case, within the stated errors, the injection index is in approximate agreement with studies of active radio galaxies (Harwood et al 2015(Harwood et al , 2016. Furthermore, simulations suggest (Kapinska et al 2015) that the observed integrated spectrum can steepen owing to mixing of electron populations.…”
Section: Discussionsupporting
confidence: 85%
“…In any case, within the stated errors, the injection index is in approximate agreement with studies of active radio galaxies (Harwood et al 2015(Harwood et al , 2016. Furthermore, simulations suggest (Kapinska et al 2015) that the observed integrated spectrum can steepen owing to mixing of electron populations.…”
Section: Discussionsupporting
confidence: 85%
“…Rottgering et al 2006, Kapinska et al 2015 and LOFAR now gives us the opportunity to investigate whether this is the case. However, precise modelling of the evolution of remnants and predicting the number of remnants in the radio sky remains challenging.…”
Section: Simulating the Population Of Active And Remnant Fri Radio Gamentioning
confidence: 99%
“…Firstly, the modelling of the radio spectrum of remnant sources provides constraints on the timescales of activity and quiescence of the radio source, i.e. on its duty cycle, and on their dynamical evolution (Kardashev 1962;Murgia et al 2011;Kaiser 2009;Kapinska et al 2015;Turner & Shabala 2015). Secondly, a better knowledge of the energetics of these objects can help quantify the role of radio AGN feedback, as well as give new insights into the formation of radio sources in galaxy clusters such as relics, brienza@astron.nl halos, and phoenixes (Slee et al 2001;Enßlin & Brüggen 2002;van Weeren et al 2009;de Gasperin et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…During its first stage of completion, the Square Kilometre Array (SKA; Dewdney et al 2009) will include two instruments: SKA1-LOW (50 -350 MHz) and SKA1-MID (350 -14 GHz) (see e.g. Kapinska et al 2015). Wide and deep radio continuum surveys with the SKA will increase the number of low redshift radio AGN by orders of magnitude and will allow us to detect radio quiet AGN of luminosities as low as log L 1 GHz ∼ 23 out to redshifts of z ∼ 6 (Smolcic et al 2015).…”
Section: Future Work and Surveysmentioning
confidence: 99%